2016
DOI: 10.4314/sajg.v5i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicle (UAV) photogrammetry produces accurate high-resolution orthophotos, point clouds and surface models for mapping wetlands

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…James and Robson, 2014;Wackrow and Chandler, 2011;Javernick et al, 2014) although the approach, has been largely overlooked in much of the geoscience literature (e.g. Boon et al, 2016;Casella et al, 2016). The results still depend on accurate pre-calibration, as errors will tend to scale with altitude of the UAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…James and Robson, 2014;Wackrow and Chandler, 2011;Javernick et al, 2014) although the approach, has been largely overlooked in much of the geoscience literature (e.g. Boon et al, 2016;Casella et al, 2016). The results still depend on accurate pre-calibration, as errors will tend to scale with altitude of the UAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little consistency, and in some cases an absence (e.g. Boon et al, 2016;Casella et al, 2016) of an examination of the camera calibration methods. Whilst a number of photogrammetry-focused studies document specifically the mitigation of errors in UAS-derived topographic modelling (Wackrow and Chandler, 2011;James and Robson, 2014;Girod et al, 2017), there is limited evidence of the incorporation of key methods such as inclusion of oblique imagery or precalibration within the broader geoscience literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harwin and Lucieer [45] suggest that a point cloud accurate to 25-40 mm can be obtained from imagery acquired from~50 m flight altitude. Other studies reported RMSEs of residuals of the bundle adjustment transformation on used GCPs as low as a few millimetres [27], or slightly over 1 cm [28], while the flight altitudes were higher-40 m and 120 m. Dandois and Ellis [36] conducted 3D mapping of vegetation dynamics with the use of Ecosynth and UAV imagery. The accuracy was calculated under leaf-on, and also leaf-off, conditions while using six GCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the method has been embraced by forest engineers because it can provide high-quality forest inventory data, which is otherwise very time-consuming to assess from the ground [12][13][14][15][16]. In addition, SfM has become the standard tool for high-precision mapping (orthophoto generation) of agricultural and natural ecosystems e.g., [10,17,18].…”
Section: Introductionmentioning
confidence: 99%